Coordination Analysis of Revenue Sharing in E-Commerce Logistics Service Supply Chain With Cooperative Distribution. (August 2019) - Zhong, Yaoguang; Guo, Fangfang; Wang, Zhiqiang; Tang, Huajun
With the rapid development of e-commerce, logistics distribution has become the bottleneck of its development. It is urgent to study how to optimize the cooperation between e-commerce platforms and logistics service providers. Based on Stackelberg game theory, this research first studies the decision making of two-stage logistics service supply chains consisting of the e-commerce mall and the logistics service provider without cooperative distribution, in which decentralization and centralization are analyzed, respectively. Then, it is extended to the decision making of three-stage logistics service supply chains consisting of e-commerce malls, express delivery companies, and terminal distributors. The results show that the profit, sales volume, and logistics service effort of the centralized decision-making system are higher than those of the decentralized decision-making system, regardless of the two-stage or three-stage logistics service supply chain. Therefore, it is vital to formulate a reasonable profit distribution scheme based on revenue-sharing contract to achieve the cooperation among the partners of logistics service supply chain, so as to achieve a win-win situation in which all of their profits increase. Finally, a numerical example is presented to verify the results, and some issues are proposed for future research.